PAR and racism - Demetriou, Loucia; Christodoulides, Paul (My University, 2003)
We investigated the link between racism/xenophobia and the seven personality dimensions (PART) Main instruments were the PAQ and a specially developed questionnaire (Q1). The p-value was determined through the two-sample chi-square test and questions of the Q1 with significant statistical correlations with PAQ scales were grouped together to form clusters. Results reveal statistically significant correlations between personality functioning and racist tendencies in attitudes and behavior. Individuals tending toward racism/xenophobia on the cognitive/behavioral level tend toward the zone of poor emotional/behavioral functioning. They show greater tendency toward hostility/aggression, low self-esteem and emotional dependency. Xenophobia is found more frequently in those individuals tending toward emotional instability and negative worldview.
Keywords: Xenophobia; Racism